Comparative analysis of mobile interfaces services to search public transport connections - Skowroński, Filip; Miłosz, Marek (Journal of Computer Sciences Institute, 2017)
Based on Nielsen's conclusions, ISO standards, and metrics efficiency, problem-based and user ratings, mobile interfaces of three applications for searching public transport connections were evaluated and compared. The research was conducted using an eye tracking goggle and surveys on a group of five students of the Lublin University of Technology. The same functionalities of applications were tested.